2020
DOI: 10.3390/cancers12113321
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Clinical Management and the Molecular Biology of Angiosarcomas

Abstract: Angiosarcomas comprise less than 3% of all soft tissue sarcomas but have a poor prognosis. Most angiosarcomas occur without obvious risk factors but secondary angiosarcoma could arise after radiotherapy or chronic lymphedema. Surgery remains the standard treatment for localized angiosarcoma but neoadjuvant systemic treatment may improve the curability. For advanced angiosarcoma, anthracyclines and taxanes are the main chemotherapy options. Anti-angiogenic agents have a substantial role but the failure of a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 132 publications
0
32
0
Order By: Relevance
“…Other investigations have also reported frequent TP53 mutations in human angiosarcomas. [ 7 9 ] Collectively, these genetic studies strongly suggest that the PI3K, MAPK, and TP53 pathways play an important role in the development of angiosarcoma. In addition, Chadwick et al reported that PTEN was largely absent in high-grade angiosarcomas, while pMAPK was activated in all tumors of vascular origin.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have also reported frequent TP53 mutations in human angiosarcomas. [ 7 9 ] Collectively, these genetic studies strongly suggest that the PI3K, MAPK, and TP53 pathways play an important role in the development of angiosarcoma. In addition, Chadwick et al reported that PTEN was largely absent in high-grade angiosarcomas, while pMAPK was activated in all tumors of vascular origin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent case series have suggested that immune checkpoint inhibitors may be active in the treatment of advanced AS [ 15 ], while the combination of VEGFR and checkpoint inhibitors, already established in the treatment of several solid tumors, also appears to be a promising treatment option in soft tissue sarcoma patients in general [ 16 ]. We therefore believe that future studies should evaluate the safety and efficacy of VEGFR and immune checkpoint inhibitors with or without paclitaxel in a randomized, multiarm setting, as is the case in the currently recruiting NCT04339738 trial [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 The results of different treatments vary widely and are affected by many factors, such as tumor location, tumor size, resectability, and tumor type. 13 , 24 , 25 According to previous studies, 26 , 27 radical surgery remains the standard therapy for localized AS among different therapeutic approaches. It is still considered to be the most valid method to improve the 5‐year survival rate of AS.…”
Section: Discussionmentioning
confidence: 99%